Reconstruction of Premaxilla With Alveolar Distraction Osteogenesis in a Patient With Complete Cleft Lip and Palate: A Case Report - (:unkn) unknown (ALLIANCE COMMUNICATIONS GROUP DIVISION ALLEN PRESS, 2019)
This case report presents an early clinical evaluation of a patient with bilateral cleft lip and palate (CLP) treated with ArchWise Distraction Osteogenesis Technique and Appliance. A 16-year-old patient with a bilateral CLP had a chief complaint of missing upper anterior teeth and poor aesthetics. The patient had class III skeletal and dental relationships, maxillary hypoplasia, maxillary posterior arch constriction, premaxillary deficiency, multiple missing teeth due to an alveolar cleft, and a concave profile. Treatment plan consisted of maxillary expansion with quad helix appliance, leveling and aligning of the arches with fixed orthodontic appliances, and archwise distraction osteogenesis. Osteotomies were performed to mobilize the posterior segments. Activation of the distractors was continued until the lateral segments had contacted each other, and then sagittal distraction was performed in order to correct the sagittal discrepancy. Patient was referred to the oral surgeon and prosthodontist for the final restorations. A very large gap was successfully repaired using this protocol while maintaining the ideal arch form and generating new bone behind the distracted segments.
Keywords: distraction osteogenesis; nonsyndromic clefting; aesthetics; INTERDENTAL DISTRACTION; DEVICE